Green Economy: Innovations and Challenges in the Transition to Sustainability - Nadia Fransiska Dewi; Fajar Ardian Nur Alif; Hwihanus Hwihanus (WANARGI : Jurnal Manajemen Dan Akuntansi, 2024)
In the last few decades, the issue of climate change and environmental degradation has encouraged the emergence of the concept of a green economy as an approach to achieving sustainable economic development without destroying the environment. The green economy concept aims to reduce environmental risks, increase resource efficiency, and encourage innovation that can support economic growth. This article discusses innovations and challenges in the green economy transition, with an emphasis on efforts towards governments and the private sector implementing sustainable practices. The analysis is carried out through case studies and literature research on green economy initiatives in several countries that have successfully incorporated green economic policies into their national development frameworks. The findings show that despite significant progress in the implementation of green technologies and innovative policies, there are still various barriers that need to be overcome, including lack of funding, resistance from certain industrial sectors, and the need for adequate infrastructure. This article also highlights the importance of multilateral cooperation and an integrated approach between sectors to increase the effectiveness of the green economic transition. It is hoped that this discussion can provide insight for policy makers, researchers and practitioners on ways to overcome these challenges and accelerate the transition to a more sustainable economy.